Canakinumab in colchicine resistant familial Mediterranean fever and other pediatric rheumatic diseases - Çakan, Mustafa; Karadağ, Şerife Gül; Ayaz, Nuray Aktay (The Turkish Journal of Pediatrics, 2020)
Background and Objectives. The aim of this observational retrospective cohort study was to demonstrate indications and response rates of the patients with pediatric rheumatic diseases that used canakinumab. Method. The files of the patients that used canakinumab between December 2012 and July 2017 were reviewed. Canakinumab was used in 29 patients. Diagnosis of the patients were; colchicine resistant familial Mediterranean fever (crFMF) (19 cases), hyperimmunoglobulin D syndrome-mevalonate kinase deficiency (HIDS-MKD) (3 cases), cryopyrin-associated periodic syndrome (3 cases), systemic juvenile idiopathic arthritis (sJIA) (2 cases), idiopathic recurrent pericarditis (1 case) and pyoderma gangrenosum (1 case). Results. Canakinumab was used for 21.8 ± 15.8 months (6-54 months). crFMF patients had a female predominance; 16 girls and 3 boys. Mean age at the first symptoms of FMF was 2.8 ± 2.2 years. Mean number of attacks per year before colchicine was 18.7 ± 6.9 (10-36), after colchicine was 8.2 ± 2.7 (6-12) and after biologic agent the number dropped to 0.1 ± 0.3 (0-1). Canakinumab led to resolution of attacks in 3 HIDS-MKD cases. Two familial cold autoinflammatory syndrome patients were using canakinumab for 13 months with total remission. Chronic infantile neurological cutaneous articular syndrome patient did not show dramatic response to standard doses of IL-1 blockers and remission was achieved with high doses of canakinumab. Canakinumab led to the resolution of all systemic and articular manifestations in one sJIA case but the other sJIA case developed polyarticular joint involvement under canakinumab treatment. A severe pyoderma gangrenosum patient that failed dapson and anakinra, also failed canakinumab treatment that was used for 9 months. We have successfully treated a case of idiopathic recurrent pericarditis with canakinumab. Canakinumab was discontinued due to inefficacy only in two cases. Conclusion. Overall efficacy of canakinumab was 93.1% in this study. No major adverse event was observed under canakinumab treatment. Canakinumab seems to be effective and safe in children with rheumatic diseases.
Keywords: autoinflammatory diseases; canakinumab; colchicine resistant familial Mediterranean fever